The Russian Factor in Turkey's Georgian Policy after the Russian-Georgian War (August 2008) - Asadov, Murad (International Journal of Scientific Research and Management (IJSRM), 2020)
Formation of new states in the South Caucasus and Central Asia after the collapse of the Soviet Union raised to have relations with the Turkic peoples of Central Asia first in the history of the Republic for Turkey. Foreign policy the Caucasus continues to evolve in its foreign policy strategy. A force associated with this well-intentioned policy, which is adjacent to the Laki region, is always offered. Whenever Turkey wants to enter the Caucasus, it will not be adversely affected by other countries. With the collapse of the Soviet Union in the 1990s, Russia's influence in the region was weak. The nickname was temporary. At the beginning of the 21st century, Vladimir Putin received a well-developed document with the credibility of Putin.Turkey’s north-east neighbour Georgia is not a very big country, it has a particular importance of the geostrategic position not only in the Caucasus region but also in Turkey. Especially, the location of Georgia in the center of the transport and trade routes to the Caucasus and Central Asia increases its geostrategic status more. The main positive turning point in the development of Georgia-Turkey relations happened with the realization of oil and natural gas pipelines to run Caspian oil through Tbilisi to Turkey and from there to the West.This article will explore the Turkish-Russian relations of the late twentieth and early twenty first century and the Russian factor in Turkey's South Caucasus policy following the August 2008 events.